An in-vitro comparison of force extension and force degradation characteristics of latex and non-latex orthodontic elastics - Karmacharya, Anjana
The purpose of this in-vitro study was to compare the force extension and force degradation characteristics of Latex Regular, Latex Colored and Non-Latex orthodontic elastics. Orthodontics elastics (1/4 inch and 6 ounce or equivalent stated force values) from three manufacturers were investigated, namely ? GAC International (Islandia, NY), American Orthodontics Inc. (Shyboygan, Wis), and Forestadent (Pforzheim, Germany). A Universal testing machine (Shimadzu AG-X, Japan) was used to record the forces measurements. Dry Test was conducted under room temperature (24 degrees C) and dry air condition to determine the force extension characteristics and breaking forces. Each of the elastics was stretched by continuous extension from 15 mm to 60 mm or until it broke. Wet Test was performed in natural saliva maintained at 37 +/- 0.01 degrees C to evaluate the force degradation characteristics of orthodontic elastics. The elastics were stretched between stainless steel pins mounted at fixed distances apart (20, 26, 32 and 40 mm) on the dental stone boards. Force measurements were made at four time intervals: 0, 1, 6 and 24 hours. Descriptive statistics, ANOVA via F-test Scheffe?s test of the pairwise mean-comparisons were performed. The level significance (p-value) used was 0.05. Among the three types of elastics, the force-extension characteristics of Latex Regular elastics were significantly greater than those of Latex Colored and Non-Latex elastics. With regards to breaking force, Latex Regular and Latex Colored elastics of Manufacturer A and B was significantly higher than Non-Latex elastics. However, the difference between Latex Regular and Non-Latex elastics was not significant for Manufacturer C with respect to breaking force. The Inter-manufacturer comparisons for both force-extension and breaking force, no single manufacturer was found to be superior to the other. In the wet test for degradation, significant difference was seen only with respect to time. There was a general trend of large initial force degradation followed by less steep force degradation slope. A significant difference was seen between 1-hour, 6-hours and 24-hours intervals. Force degradation among the various manufacturers and types of elastics was not significantly different. Based on the findings of the study, it can be concluded that the mechanical properties of Non-Latex elastics cannot be assumed to be and indeed are not the same as those of Latex elastics. To provide the orthodontists with a more consistent means of delivering force over an extended period of time, an improvement of physical properties of the Non-Latex elastics are required. Therefore, the clinical choice of elastics should be based on the patient?s medical history and the specific mechanical properties of the type of elastics.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Orthodontic appliances; Dental bonding; Orthodontics